Istiratijiyyat Haqibah al-Injaz fi Ta’lim al-Kitabah lada Thalabah al-Barnamaj al-Mukatstsaf li Ta’lim al-Lughah al-Arabiyah bi Jami’ah Maulana Malik Ibrahim al-Islamiyah al-Hukumiyah Malang. - Nur Arifuddin; Asmaul Husna; Fahmi Shihab Az zamzami (UIN Maulana Malik Ibrahim Malang, 2022)
Writing is one of the four language skills that students and the last language skill in language learning. Even in the academic field, especially at the university level, the urgency of these skills is very large in learning activities, which we know that student work requires writing skills, especially for writing a thesis and dissertation. At the tertiary level, learning writing skills is divided into three stages: directed writing, free writing, and academic writing. This research uses a descriptive method. The data collection technique uses document techniques, in-depth interviews and participant observation. The results of this study are; First: Teachers of the Arabic Language Development Program have conducted an evaluation using a portfolio strategy in learning to write to obtain information about the results of student assignments. The teacher / lecturer implements this strategy by collecting all student work during the learning process, which contains the work results that have been checked by the lecturer and corrected by the students according to the notes given. Second: the positive factor of this strategy is to improve students' ability to evaluate themselves during the writing process, and students can learn from their mistakes and be able to improve their independent writing competence. The negative factors are the problems in the students' writing examination activities which are divided into three parts; the timing is not right, the students 'writing is not understandable, and the assignments are not in accordance with the lecturers' instructions. One of the obstacles faced by the lecturer in determining the results is when the assignments that have been collected by students are put into a portfolio containing paper folders, while some paper assignments are not put in that folder.